2019
DOI: 10.1088/1361-6560/ab051c
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of different x-ray Talbot–Lau setups for dark-field lung imaging examined in a porcine lung

Abstract: X-ray dark-field imaging is a promising technique for lung diagnosis. Due to the alveolar structure of lung tissue, a higher contrast is obtained by the dark-field image compared to the attenuation image. Animal studies indicate an enhancement regarding the detection of lung diseases in early stages. In this publication, we focus on the influence of different Talbot-Lau interferometer specifications while maintaining the x-ray source, sample magnification and detector system. By imaging the same porcine lung w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 66 publications
0
15
0
Order By: Relevance
“…Based on this evaluation, the design parameters as stated in Table I have been derived and the resulting design yields a correlation length of 0.22 µm. While this cannot reach the challenging correlation length criterion demanded by [16] (this would require a 1.0 µm fine G 0 which is currently not feasible to fabricate), this leaves the proposed dark-field CT design at around half the sensitivity of the dark-field chest radiography system [20] which is operating successfully in clinical routine. We are confident that the tomographic reconstruction allows us to compensate for this drawback, as the volume reconstruction allows us to work with advanced processing and filtering approaches not applicable in radiographic imaging.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on this evaluation, the design parameters as stated in Table I have been derived and the resulting design yields a correlation length of 0.22 µm. While this cannot reach the challenging correlation length criterion demanded by [16] (this would require a 1.0 µm fine G 0 which is currently not feasible to fabricate), this leaves the proposed dark-field CT design at around half the sensitivity of the dark-field chest radiography system [20] which is operating successfully in clinical routine. We are confident that the tomographic reconstruction allows us to compensate for this drawback, as the volume reconstruction allows us to work with advanced processing and filtering approaches not applicable in radiographic imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Another important design measure in dark-field setups is the correlation length ξ, which can be calculated from the sensitivity [16], [32]- [34]:…”
Section: Talbot-lau Interferometer Geometriesmentioning
confidence: 99%
See 1 more Smart Citation
“…The microfocal X-ray source [7] or even a traditional X-ray tube can be used as the source [8,9]. This extends the application of X-ray phase contrast imaging technology [10][11][12][13]. In this technique, the spatial harmonic method is a variant grating-based method where absorption, differential phase contrast, and dark-field can be obtained from a single raw image [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…With the introduction of Talbot-Lau imaging to the laboratory by Pfeiffer et al [50,49], many more examples have been shown. Applications of X-ray darkfield imaging besides the characterization of micro-calcifications in mammography [38,15] include imaging of lungs [71,61,17,32], characterization of bone and dentin [51,43,27,26,21] as well as the analysis of general porous and fibrous materials or microscopic defects in the field of non destructive testing [54,24,16]. Other applications that have been shown include water transport in cement [52,70] or the monitoring of germinating seeds [44].…”
Section: Introductionmentioning
confidence: 99%